Competitiveness of Small Towns: Role of Town-Planning Culture Traditions in Residential Area - T. T. Kuznetsova (Наука и техника, 2003)
Due to reduction of centralized investments it is necessary to integrate small towns into the system of market relations. In this case a town with all its particulars is to be considered as a commodity. Peculiar features of residential area that constitute the basis of the context of historical and cultural potential of small towns may serve as an active part of their competitive advantage.The paper considers traditions of town-planning culture at the residential building as a sustainable basis of the environmental variety of small towns.